Implementation Of Customary Law Values In Abui Tribal Customary Marriage In Realizing Laws Based On Local Wisdom - Lay, Benediktus Peter; Rade, Stefanus Don; Geme, Maria Theresia (UNIVERSITAS PAKUAN, 2024)
The problem that drives this research is first, customs and marriage ceremonies will still exist in a cultured society, although within the limits of time and space will undergo changes. Second, customs and marriage ceremonies are cultural elements that are lived from time to time, and inclusive and strong values and norms regulate and direct the behavior of each individual in a society. The approach chosen is a variation between approaches in normative research and empirical research so that historical, conceptual, philosophical, and case approaches are chosen. The customary law of marriage in the Abui Tribe is one of the ancestral cultural products of the Abui Tribe that must be maintained and maintained properly to preserve the continuity of noble cultural values as a local wisdom loaded with messages of virtue. This study aims to see the implementation of customary law procedures for customary marriage of the Abui Tribe and the values contained in customary marriage of the Abui Tribe. Hopefully, this research can contribute to marriage law in a constitutional system based on local wisdom.